2017
DOI: 10.1038/srep41682
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based quantitative proteomic analysis of the global response to 17β-estradiol in estrogen-degradation strain Pseudomonas putida SJTE-1

Abstract: Microorganism degradation is efficient to remove the steroid hormones like 17β-estradiol (E2); but their degradation mechanism and metabolic network to these chemicals are still not very clear. Here the global responses of the estrogen-degradation strain Pseudomonas putida SJTE-1 to 17β-estradiol and glucose were analyzed and compared using the iTRAQ (isobaric tags for relative and absolute quantization) strategy combined with LC-MS/MS (liquid chromatography-tandem mass spectrometry). 78 proteins were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The protein quantification was performed using the IQuant software [13]. The following criteria were used for screening differentially expressed proteins: fold change ≥1.5 or ≤0.67 and p value ≤0.05 [14]. Functional annotations were further conducted by searching these proteins against the KEGG (http://www.genome.jp/kegg/pathway.html), eggNOG (http://eggnogdb.embl.de/), and WoLF PSORT databases (https://wolfpsort.hgc.jp/) [15].…”
Section: Methodsmentioning
confidence: 99%
“…The protein quantification was performed using the IQuant software [13]. The following criteria were used for screening differentially expressed proteins: fold change ≥1.5 or ≤0.67 and p value ≤0.05 [14]. Functional annotations were further conducted by searching these proteins against the KEGG (http://www.genome.jp/kegg/pathway.html), eggNOG (http://eggnogdb.embl.de/), and WoLF PSORT databases (https://wolfpsort.hgc.jp/) [15].…”
Section: Methodsmentioning
confidence: 99%
“…The high degradation efficiency of E2 by strain MZT7 was attributed to the abundance of transporter proteins in its genome ( Figure 3 and Figure S4 ). Xu et al reported that the ABC transporter is involved in the uptake and transport of steroids [ 47 ]. Further, strain MZT7 has good tolerance to complex environments, including pH (5.0–11.0), temperature (20–40 °C), and salinity (8%).…”
Section: Resultsmentioning
confidence: 99%
“…The STRING analysis reveals the relations hidden behind the changes of protein levels by means of a computer-assisted analytical approach ( Xu et al, 2017 ). In this study, the protein–protein relationships within the DEPs were also examined using STRING.…”
Section: Discussionmentioning
confidence: 99%